Pengembangan Evidence Monitoring Tingkat PH dan Kekeruhan Air Untuk Menentukan Kelayakan Konsumsi Air - Andi Fatri; Muhammad Basri; Untung Suwardoyo (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2024)
Development of Evidence Monitoring of PH Levels And Water Turbidity to Determine the Feasibility of Water Consumption. (Supervised by Muhammad Basri and Untung Suwardoyo). The most common method for detecting water quality parameters is by manually collecting samples and sending them to a laboratory for detection and analysis. However, with the advancement of time and technology, this method has become somewhat less relevant due to its manual nature. For that reason, a study was conducted titled